2019
DOI: 10.1136/bmjopen-2019-033919
|View full text |Cite
|
Sign up to set email alerts
|

Variation in survival after out-of-hospital cardiac arrest between receiving hospitals in Japan: an observational study

Abstract: ObjectivesPatient outcomes after out-of-hospital cardiac arrest (OHCA) varies at multilevel (geographical regions, emergency medical service agencies and receiving hospitals) in the USA. However, it remains unclear whether there is a variation in patient outcomes after OHCA between relevant units of the healthcare system such as receiving hospitals in Japan. Therefore, we aimed to quantify the variation in patient outcomes after OHCA between receiving hospitals in Japan.DesignSecondary analysis of the prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The rate of survival to hospital discharge of 18.8% in all-cause OHCA patients observed in this study is also comparable to the majority of previously reported rates in recently published studies [ 2 , 3 ], as well as 30-day survival rate which is comparable with the values observed in other countries and reported in ERC Guidelines 2021 [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The rate of survival to hospital discharge of 18.8% in all-cause OHCA patients observed in this study is also comparable to the majority of previously reported rates in recently published studies [ 2 , 3 ], as well as 30-day survival rate which is comparable with the values observed in other countries and reported in ERC Guidelines 2021 [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…The prognosis of out-of-hospital cardiac arrest (OHCA) is very poor, with the survival rate ranging from 2 to 11% in the Asia-Pacific area [1]. Many prehospital factors influence the outcomes of OHCA, such as witnessing the OHCA, bystander cardiopulmonary resuscitation (CPR), initial heart rhythm, level of hospital care, location, and time of OHCA [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Many prehospital factors might influence the outcomes of OHCA, such as location of OHCA, witnessed arrest, bystander cardiopulmonary resuscitation (CPR), initial cardiac rhythm, and level of post-resuscitation care [ 3 6 ]. The emergency medical service (EMS) response time is defined as the time interval between the call made to the EMS and the arrival of the EMS team at the scene.…”
Section: Introductionmentioning
confidence: 99%